Gas emissions and crustal deformation from the Krýsuvík high temperature geothermal system, Iceland - Gudjónsdóttir, Sylvía Rakel; Ilyinskaya, Evgenia; Hreinsdóttir, Sigrún; Bergsson, Baldur; Pfeffer, Melissa Anne; Michalczewska, Karolina; Aiuppa, Alessandro; Óladóttir, Audur Agla (Journal of Volcanology and Geothermal Research, 2020)
The Krýsuvík volcanic system is located on the oblique spreading Reykjanes Peninsula, SW Iceland. Since early 2009 the region has been undergoing episodes of localized ground uplift and subsidence. From April–November 2013, we operated near-real time monitoring of gas emissions in Krýsuvík, using a Multi-component Gas Analyzer System (Multi-GAS), collecting data on gas composition from a fumarole (H2O, CO2, SO2, H2S). The dataset in this study, comprises a near-continuous gas composition time series, the quantification of diffuse CO2 gas flux, analytical results for direct samples of dry gas, seismic records, and GPS data. Gas emissions from the Krýsuvík geothermal system were examined and compared with crustal deformation and seismicity. The gas emissions from the Krýsuvík system are H2O-dominated, with CO2 as the most abundant dry gas species, followed by smaller concentrations of H2S. The average subsurface equilibrium temperature was calculated as 278 °C. This is consistent with previous observations made through sporadic spot sampling campaigns. In addition, the semi-continuous Multi-GAS dataset reveals higher variations in gas composition than previously reported by spot sampling. The diffuse soil CO2 flux is found to be variable between the three studied degassing areas in Krýsuvík, ranging from 10.9–70.9 T/day, with the highest flux in Hveradalir where the Multi-GAS station is located. The total flux is estimated as 101 T/day. Comparison between Multi-GAS and geophysical data shows that peaks of H2O-rich emissions appears to follow crustal movements. Coinciding with the H2O-rich peaks, SO2 is detected in minor amounts (~0.6 ppmv), allowing for calculations of H2O/SO2, CO2/SO2 and H2S/SO2 ratios. This is the first time SO2 has been detected in the Krýsuvík area. The large variations in H2O/CO2 and H2O/H2S ratios are considered to reflect variable degassing activity in the fumarole. The activity of the fumarole appears less intense during intervals of low or no recorded seismic events. The H2O/CO2 and ...